THE APPLICATION OF NANOMECHANICS IN ENERGY TECHNOLOGIES - Avsec, Jurij; Novosel, Urška (Journal of Energy Technology, 2024)
Nanotechnologies may be very efficient for improving and optimizing energy technologies. The following will be shown in this paper: nanomaterials are very important in energy technology. Nanofluids and nanostructured materials may be applied in refrigerators, heaters, and similar equipment. In the micro- and nano-regions, the classic laws of mechanics are insufficiently accurate for the calculation of characteristics and properties. In this article, the application of microfluidics and vibration theory in the micro and nano-regions will be shown.